Traffic Anomaly Detection. Issue 6 (June 2016) - Unknown
Abstract : It seems an obvious statement, but the traffic you don't want on your networks – the malicious traffic from malware and intruders – simply shouldn't be there. It's traffic that doesn't form part of the normal picture of the normal, day-to-day activity. You'd think, then, that it would be easy to spot – assuming that you're looking in the right places.